The Urgency of Implementing Gender Responsive Budgets in Local Governments (Study in Sidoarjo Regency): Urgensi Penerapan Anggaran Responsif Gender Di Pemerintah Daerah (Studi Pada Kabupaten Sidoarjo) - Biduri, Sarwenda; Dewi, Santi Rahma; usrotin, Ilmi (Procedia of Social Sciences and Humanities, 2022)
This study aims to find out why the local government does not respond to gender responsive budgeting. Since the issuance of the regulation known as Presidential Instruction No. 9/2000, there has been no significant change in gender equality. This research builds on several previous studies in Indonesia which found that many regulations have been established to promote gender equality, but no significant action has been shown by local governments to implement them. So, this study tries to find out what obstacles hinder the implementation of gender responsive budgeting in local governments. This research method is descriptive quantitative. An in-depth documentation study is a tool for collecting data. This study found several obstacles such as understanding of the concept of gender among government officials, political will, and resistance to change. Some strategies to overcome this obstacle are (1) affirmation of political commitment; (2) affirmation of technical capacity. The contributions of this research include developing theory in public sector accounting especially in the budgeting process, and providing an understanding of gender responsive budgeting in local government. The last important contribution is to provide advice and an overview for the Sidoarjo City Government to start implementing gender responsive budgeting.